2020
DOI: 10.1038/s41598-020-63910-y
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and psychopathology of vegetarians and vegans – Results from a representative survey in Germany

Abstract: The aim of the study was to investigate the prevalence of, and attitudes toward, vegetarianism and veganism. We also assessed the association between vegetarianism/veganism and eating disorder, depressive, and somatic symptoms. A cross-sectional questionnaire survey in adults in Germany that was representative in terms of age, gender, and educational level was carried out. Data from 2449 adults (53.5% females) were included. Mean age was 49.6 (SD 17.1) years. A total of 5.4% of participants reported following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 53 publications
(94 reference statements)
12
70
1
10
Order By: Relevance
“…Moreover, for many vegetarians, concern about the ethics of raising and slaughtering animals may be a central motivation (35) which could also affect their response to a question on their own happiness because of the empathic inclusion of animals. Our study also showed that vegetarians had better self-reported health than non-vegetarians, and that they displayed lower BMIs, which is consistent with previous studies (36,37,38) . However, some limitations affecting this study need to be discussed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, for many vegetarians, concern about the ethics of raising and slaughtering animals may be a central motivation (35) which could also affect their response to a question on their own happiness because of the empathic inclusion of animals. Our study also showed that vegetarians had better self-reported health than non-vegetarians, and that they displayed lower BMIs, which is consistent with previous studies (36,37,38) . However, some limitations affecting this study need to be discussed.…”
Section: Discussionsupporting
confidence: 92%
“…While the replacement of meat products with vegetarian diets lowers the risk of cardiovascular issues, obesity, and diabetes, and is considered by the Academy of Nutrition and Dietetics as nutritionally adequate when appropriately planned, and even potentially bene cial for health (4) , the bene ts to mental health remain widely discussed. Many studies have indicated that individuals with low meat consumption or a vegetarian diet are exposed to an increased risk of depression (5,6,7,8) . Such results have commonly been understood as the outcome of potential nutritional de cits in vitamin B12, long-chain n-3 fatty acids, folates, and/or zinc (9,10,11) .…”
Section: Introductionmentioning
confidence: 99%
“…Veganism, covering a variety of diet patterns that involve the avoidance of meat, has gained increasing popularity and represents a growing social movement [ 135 ]. Adherence to a vegan diet, even if only for short periods (7 weeks), might beneficially affect several cardiovascular risk factors [ 136 , 137 ], including BW, body mass index, systolic and diastolic blood pressure, total and high-density cholesterol, and C-reactive protein, as well as ameliorate the quality of life [ 137 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Given the higher prevalence of osteoporosis [ 36 ], iron deficiency [ 37 ], and thyroid disorders [ 38 ] in female patients, our findings are concordant with epidemiologic disease distribution. The higher testing rate of vitamin B12 in female patients is less obvious to understand and may be linked to anemia investigations being more frequent in female patients due to iron deficiency and, in addition, to female sex being associated with vegetarian or vegan diet requiring vitamin B12 monitoring [ 39 ]. These factors, however, do not explain the high between-GP variation in vitamin B12 testing rates.…”
Section: Discussionmentioning
confidence: 99%